The effect of omega-3 fatty acids on a biomarker of head trauma in NCAA football athletes: a multi-site, non-randomized study - Heileson, J. L.; Anzalone, A. J.; Carbuhn, A. F.; Askow, A. T.; Stone, J. D.; Turner, S. M.; Hillyer, L. M.; Ma, D. W. L.; Luedke, J. A.; Jagim, A. R.; Oliver, J. M. (Journal of the International Society of Sports Nutrition, 2021)
Background: American-style football (ASF) athletes are at risk for cardiovascular disease (CVD) and exhibit elevated levels of serum neurofilament light (Nf-L), a biomarker of axonal injury that is associated with repetitive head impact exposure over the course of a season of competition. Supplementation with the w-3 fatty acid (FA) docosahexaenoic acid (DHA) attenuates serum Nf-L elevations and improves aspects of CVD, such as the omega-3 index (O3I). However, the effect of combining the w-3 FA eicosapentaenoic acid (EPA) and docosapentaenoic acid (DPA) with DHA on, specifically, serum Nf-L in ASF athletes is unknown. Therefore, this study assessed the effect of supplemental w-3 FA (EPA+DPA+DHA) on serum Nf-L, plasma w-3 FAs, the O3I, and surrogate markers of inflammation over the course of a season. Methods: A multi-site, non-randomized design, utilizing two American football teams was employed. One team (n = 3 1) received supplementation with a highly bioavailablew-3 FA formulation (2000mg DHA, 560mg EPA, 320mg DPA, Mindset®, Struct Nutrition, Missoula, MT) during pre-season and throughout the regular season, while the second team served as the control (n = 35) and did not undergo supplementation. Blood was sampled at specific times throughout pre- and regular season coincident w ith changes in intensity, physical contact, and changes in the incidence and severity of head impacts. Group differences were determined via a mixed-model between-within subjects ANOVA. Effect sizes were calculated using Cohen`s dfor all between-group differences. Significance was set a priori at p< .05. Results: Compared to the control group, ASF athletes in the treatment group experienced large increases in plasma EPA (p < .001, d = 1.71) and DHA (p < .001, d = 2.10) which contributed to increases in the O3I (p < .001, d = 2.16) and the EPA:AA ratio (p = .001, d = 0.83) and a reduction in the w-6: w-3 ratio (p < .001, d = 1.80). w-3 FA supplementation attenuated elevations in Nf-L (p = .024). The control group experienced a significant increase in Nf-L compared to baseline at several measurement time points (T2, T3, and T4 [p range < .001 - .005, drange = 0.59-0.85]). Conclusions: These findings suggest a cardio- and neuroprotective effect of combined EPA+DPA+DHA w-3 FA supplementation in American-style football athletes.